Rainfall induced residual soil slope instability : building cracked and slope failure - Lee, Jing Yue (2018)
Rainfall is one of the factors for slope failures because intensity of rainfall will affect by seeping, moisture content of soil or matric suction. One of the important role in slope stability is matric suction. The slope stability analysis involved a building which may cause by instability due to suction variation. This study presents the relationship between rainfall and suction of soil which induced the slope instability. The slope had separated into three parts which are top of slope, middle of slope and toe of slope. Every part will insert three tensiometer with 0.3 m, 0.45 m and 0.9 m depth. Suction of soil on slope was carried out by using tensiometer. Reading for matric suction of soil was taking daily in the morning which from 3rd August 2017 until 15th August 2017. Intensity of rainfall was collected by using rain gauge which placed at open area. The daily intensity of rainfall for 13 days was compared with matric suction of soil. The rainfall had affected suction of soil. On 7th August 2017, the intensity of rainfall was high which is 15.6 mm while the matric suction value at these three parts was low. Several site and laboratory tests were carried out to identify the soil properties. Stability of slope was analyzed using Slope/w and Excel by insert parameters collected from laboratory test and field test. In excel, Fellenius’ method with formula was used to interpret the factor of safety for slope study. The factor of safety at middle of slope by using slope/w method was 1.963 while by excel was 2.65, the percentage different for it was 25.92. Fellenius’ method was used for analyses the factor of safety of slices selected with its matric suction value. The factor of safety for middle and toe of slope was below than 1.3, so the slope is unstable. From the analysis, when the rainfall increased, suction of soil decreased and affected the decreased in factor of safety. It suggested the slope need to be reconstruct and redesign.